2011
DOI: 10.1111/j.1553-2712.2011.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness of Nationally Certified Emergency Medical Services Professionals

Abstract: Objectives: During disasters, the public expects that emergency care will be available at a moment's notice. As such, an emergency medical services (EMS) workforce that is trained and prepared for disasters is imperative. The primary objectives of this study were to quantify the amount of individual-level training EMS professionals receive in terrorism and disaster-preparedness, as well as to assess EMS professionals' participation in multiagency disaster drills across the United States. Characteristics of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
(30 reference statements)
1
25
0
1
Order By: Relevance
“…Trials of a similar model have been undertaken in the municipal health services and show that the participants subsequently have better confidence in their own roles [19]. Moreover, it has been demonstrated that the sense of coping increases in pace with the amount of training [20]. One of the conclusions drawn after the Sleipner accident was that realistic exercises ought to be undertaken in which focus should be placed on cooperation with other agencies [16].…”
Section: Discussionmentioning
confidence: 99%
“…Trials of a similar model have been undertaken in the municipal health services and show that the participants subsequently have better confidence in their own roles [19]. Moreover, it has been demonstrated that the sense of coping increases in pace with the amount of training [20]. One of the conclusions drawn after the Sleipner accident was that realistic exercises ought to be undertaken in which focus should be placed on cooperation with other agencies [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, appropriate response and short time intervals (response time, scene time and evacuation time) together with adequate care are the most important aims for EMS (7-10). These systems are also the backbone of disaster response and should build such preparedness on their daily activities (11, 12). The impact of time intervals has been discussed in many studies, published during last decades (13-16).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the correlation between the number of hours of training between paramedics and fire personnel practicing for major incidents and disasters and the perceived preparedness for these events showed that the level of perceived preparedness increased with the number of hours practiced [12]. Exercises and interactions between individuals, teams and organizations have a significant impact of the effectiveness of an emergency response [13].…”
Section: Discussionmentioning
confidence: 99%